Impact of Diamond-like Carbon Films on Reverse Torque: Superior Performance in Implant Abutments with Internal Conical Connections - Coelho, Arianne Vallim Pinto [UNESP]; Figueiredo, Viviane Maria Gonçalves de [UNESP]; Ferreira, Leandro Lameirão; Silva, Alecsandro de Moura; Oliani, Marcelo Gallo; Queiroz, José Renato Cavalcanti de; Sobrinho, Argemiro Soares da Silva; Nogueira Junior, Lafayette [UNESP]; Prado, Renata Falchete do [UNESP] (MDPI, 2024)
The loosening or fracture of the prosthetic abutment screw is the most frequently reported complication in implant dentistry. Thin diamond-like carbon (DLC) films offer a low friction coefficient and high wear resistance, functioning as a solid lubricant to prevent the weakening of the implant–abutment system. This study evaluated the effects of DLC nanofilms on the reverse torque of prosthetic abutments after simulated chewing. Abutments with 8° and 11° taper connections, with and without DLC or silver-doped DLC coatings, were tested. The films were deposited through the plasma enhanced chemical vapor deposition process. After two million cycles of mechanical loading, reverse torque was measured. Analyses with scanning electron microscopy were conducted on three samples of each group before and after mechanical cycling to verify the adaptation of the abutments. Tribology, Raman and energy-dispersive spectroscopy analyses were performed. All groups showed a reduction in insertion torque, except the DLC-coated 8° abutments, which demonstrated increased reverse torque. The 11° taper groups experienced the most torque loss. The nanofilm had no significant effect on maintaining insertion torque, except for the DLC8 group, which showed improved performance.
Keywords: dental implant abutment connection; dental implants; diamond-like carbon nanofilm; torque